2004
DOI: 10.1128/aac.48.8.2787-2792.2004
|View full text |Cite
|
Sign up to set email alerts
|

Hazard Ratio in Clinical Trials

Abstract: 3Time-to-event curves analyzed by Cox proportional hazards regression are commonly used to describe the outcome of drug studies. This methodology has the advantage of using all available information, including patients who fail to complete the trial, such as in cancer chemotherapy or human immunodeficiency virus antiviral treatment studies. The goal of treatment in such studies may be to prevent the development of a complication, for example, Pneumocystis carinii pneumonia, and to describe the likelihood of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
289
0
5

Year Published

2006
2006
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 426 publications
(300 citation statements)
references
References 12 publications
6
289
0
5
Order By: Relevance
“…This high HR implies that a patient with an ALC-15 <350 cells/lL has an 83% higher probability of recurrence compared with a patient with an ALC-15 350 cells/lL. 28 Although treatment intensity might be expected correlate inversely with ALC and outcome, we found that treatment on a high-risk pediatric protocol (primarily CCG-1961) or Hyper-CVAD did not alter the significance of the ALC-15 (HR 7.8, P 5 .005; Table 3). Although patients treated on the high-risk pediatric protocols had a reasonably high HR 3.7, as expected, the P-value was not significant in our cohort.…”
Section: Alc Predicts Survival In Allmentioning
confidence: 99%
“…This high HR implies that a patient with an ALC-15 <350 cells/lL has an 83% higher probability of recurrence compared with a patient with an ALC-15 350 cells/lL. 28 Although treatment intensity might be expected correlate inversely with ALC and outcome, we found that treatment on a high-risk pediatric protocol (primarily CCG-1961) or Hyper-CVAD did not alter the significance of the ALC-15 (HR 7.8, P 5 .005; Table 3). Although patients treated on the high-risk pediatric protocols had a reasonably high HR 3.7, as expected, the P-value was not significant in our cohort.…”
Section: Alc Predicts Survival In Allmentioning
confidence: 99%
“…However, for some publications, HR and 95% CI needed to be calculated again according to the method recommended in literature (Parmar et al, 1998;Spruance et al, 2004). In order to estimate the HR value, included studies had to report the number of patients according to different XRCC1 genotype, along with the number of observed deaths/cancer recurrences.…”
Section: Data Extractionmentioning
confidence: 99%
“…The log-rank test was used to evaluate if survival curves differed significantly and the hazard ratio (HR) was calculated for each gene expression. Odds derived from the HR were calculated according to Spruance et al 23 To determine if PI3 and CHI3L1 were independent markers from other prognostic factors, a Cox regression for survival analysis was performed. Survival analysis was adjusted for age (continuously) and sex for PI3 or CHI3L1 using the same cut-off values as for Kaplan-Meier analysis, and HRs were calculated (SAS V9.1, Cary, NC).…”
Section: Gene Expression Correlation and Survival Analysismentioning
confidence: 99%